2023
DOI: 10.1101/2023.02.20.529252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards estimating the number of strains that make up a natural bacterial population

Abstract: What a strain is and how many strains make up a natural bacterial population remain elusive concepts despite their apparent importance for assessing the role of intra-population diversity in disease emergence or response to environmental perturbations. To advance these concepts, we sequenced 138 randomly selectedSalinibacter ruberisolates from two solar salterns and assessed these genomes against companion short-read metagenomes from the same samples. The distribution of genome-aggregate average nucleotide ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 34 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…The term genomovar was originally used to name distinct genomic groups within species that cannot be distinguished phenotypically from each other and therefore cannot be classified as distinct species based on the standard taxonomic practices ( 33 ). Hence, genomovar may capture conceptually well the 99.5% ANI groups, as we also proposed recently elsewhere ( 11 ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The term genomovar was originally used to name distinct genomic groups within species that cannot be distinguished phenotypically from each other and therefore cannot be classified as distinct species based on the standard taxonomic practices ( 33 ). Hence, genomovar may capture conceptually well the 99.5% ANI groups, as we also proposed recently elsewhere ( 11 ).…”
Section: Resultssupporting
confidence: 79%
“…To circumvent some of these limitations, we have recently proposed a definition threshold for strain at 99.99% ANI based on the high gene-content similarity among genomes related at this level (>99.0% of total genes, typically) and thus, phenotypic relatedness. This study was based on comparisons among 162 coexisting Salinibacter ruber isolate genomes recovered from two saltern sites in Spain ( 11 ). Testing this definition with a larger collection of genomes and how it precisely relates to STs and CCs has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1A only shows the genomes sharing OBC-types. A somewhat expected observation was that in most cases SAGs sharing the OBCs were also >99 % AAI overall i.e., they belonged to the same clonal frame or genomovar (1). This result was not surprising, since this is the fundament of strain serotyping of Gram-negative bacteria using O-antigens (12, 44).…”
Section: Resultsmentioning
confidence: 95%
“…What is the relevance of arms race processes then? In the Enterobacteriales, the gain or loss of a small number of genes (13) has been described within relatively short (epidemiological) timescales (19). Experimental studies have shown that isolated SNPs can make a strain resistant to one phage and also very small variations in the phage receptor-binding protein can revert the resistance (67).…”
Section: Discussionmentioning
confidence: 99%
“…No other pronounced ANI gap within the 300 evaluated species was consistently observed, and thus we recommend the use of the term strain only for nearly identical genomes. Specifically, we propose to define a strain as a collection of genomes sharing ANI > 99.99% based on the high gene content similarity observed at this level based on the genomes compared; for example, typically, >99.0% gene content is shared (Viver et al 31 and Table 1). It should be mentioned, however, that a 1% gene content difference for a 5 Mbp genome (e.g., E. coli 's average genome size) translates to 50 genes, which represents a substantial (nontrivial) gene content difference and could underlie significant phenotypic differences such as different antibiotic resistance profiles and plasmid DNA content 28 .…”
Section: An Ani Gap Within Species To Define Subspecies Unitsmentioning
confidence: 99%